Modulatory Role of Silver Nanoparticles and Mesenchymal Stem Cell–Derived Exosome-Modified Barrier Membrane on Macrophages and Osteogenesis - Lu, Haiping; Zhang, Yi; Xiong, Shan; Zhou, Yinghong; Xiao, Lan; Ma, Yaping; Xiao, Yin; Wang, Xin (Frontiers in Chemistry, 2021)
BACKGROUND: As a wound dressing and barrier membrane, surface modification of Polycaprolactone (PCL) is needed in order to achieve better biological activities. Exosomes derived from mesenchymal stem cells (MSCs) hold significant tissue regeneration promise. Silver nanoparticles (Ag) has been suggested as surface modification technique for various medical devices. MATERIALS AND METHODS: Ag and MSCs-derived exosomes were used to modify the PCL scaffold. The impact of different scaffolds on immune cells and MSCs proliferation and differentiation was further evaluated. RESULTS: Human MSCs derived exosomes (MSCs-exo) exhibited cup-shaped morphology with a diameter around 100 nm. MSCs-exo were enriched with exosome markers CD81 and showed good internalization into recipient cells. 200 ng/mL Ag nanoparticles and MSCs-exo were further used to modify the PCL scaffold. The internalization study further indicated similar releasing pattern of exosomes from Ag/MSCs-exo hybrid scaffolds into RAW264.7 and hBMSCs at 12h and 24h. Macrophages play an important role during different stages of bone regeneration. The MTT and confocal microscopy study demonstrated no significant toxicity of exosome and/or Ag hybrid scaffolds for macrophages and MSCs. Inflammatory macrophages were further used to mimic inflammatory environment. A mixed population of elongated and round morphology were noted in exosome and Ag hybrid group, which the pro-inflammatory genes and secretion of IL-6 and TNF-α were significantly reduced. In addition, the exosome and Ag hybrid scaffolds could significantly boost the osteogenic differentiation of hBMSCs. DISCUSSION: This study highlights the possibility of using Ag nanoparticles and MSCs-exo to modify PCL scaffold, thus providing new insight into the development of novel immunomodulatory bio-membrane.